PERANCANGAN SISTEM PENGENDALIAN PROSES UNTUK PRODUKSI MINYAK DIESEL MELALUI PIROLISIS OLI BEKAS - Riny Yolandha Parapat; Grace Rafael Haloho; Nola Septiani Pramita (PT. Hasba Edukasi Mandiri, 2026)
Waste lubricating oil is classified as hazardous and toxic waste (B3) with the potential to cause environmental pollution; however, it still contains hydrocarbon fractions with significant energy value that can be utilized as liquid fuel through a pyrolysis process. In the preliminary design of a diesel oil production system from waste oil pyrolysis, process control becomes a critical aspect due to the high operating temperatures and the involvement of gas formation and significant phase changes. This paper presents the design of a process control system for converting waste lubricating oil into diesel oil through pyrolysis. The main variables analyzed include temperature, pressure, feed flow rate, and reaction residence time, as well as supporting variables in the product separation units. The results indicate that the implementation of an integrated process control system is capable of maintaining operational stability, enhancing process safety, and preserving the quality and continuity of diesel oil production. Therefore, the proper design of a process control system at the preliminary stage plays an important role in supporting safe, stable, and efficient plant operation.